Analisis Keterlaksanaan Pembelajaran Berdiferensiasi di Kelas VII SMP X - Effi Juliana Br Tambun (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to analyze the implementation of differentiated learning in class VII at SMP Negeri X which applies the independent curriculum. The research approach used is qualitative with a field study approach. Data were obtained through observations of mathematics teachers who teach class VII. The results of the study indicate that teachers have implemented differentiated learning, by dividing students based on their level of learning readiness and adjusting the learning process and products according to student needs. Teachers divide students into groups based on their learning readiness: groups that have not understood the material, groups that understand some of the material, and groups that have understood the material. Each group receives different guidance according to their level of understanding, and is given different practice questions in terms of number and level of difficulty. However, teachers face various challenges in implementing differentiated learning, especially in terms of classroom management, limited resources, and time allocation. Teachers have difficulty in managing study groups with different levels of readiness, motivating students to work together in groups, and providing adequate LKPD for each group. To overcome these problems, this study recommends increasing teacher training in differentiated learning strategies and classroom management, providing adequate resources, and creating LKPD with varying levels of difficulty according to the learning readiness group. These solutions are expected to help teachers optimize the implementation of differentiated learning in the classroom.